Iodine catalyzed one-pot four component synthesis of coumarinyl phosphoramidates via sequential addition of reactants. (27th October 2020) - Imrankhan, Mohammed; Shivashankar, Kalegowda
Abstract : An unprecedented synthetic route for the preparation of a library of novel coumarinyl phosphoramidate derivatives via iodine catalysed one-pot four component reactions of ethyl 4-bromo-3-oxo-alkanoate, sodium azide, trialkyl phosphites, and phenols in ethanol is reported. Abstract : An unprecedented synthetic route for the preparation of a library of novel coumarinyl phosphoramidate derivatives via iodine catalysed one-pot four component reactions of ethyl 4-bromo-3-oxo-alkanoate, sodium azide, trialkyl phosphites, and phenols in the ethanol solvent is reported here. The reaction proceeds via the nucleophilic substitution reaction, phosphoramidate rearrangement and Pechmann cyclization with C–C, C–O, C–N and N–P bond formation. The prominent features of this procedure are simple one-pot operation, cost effective, non-toxic and excellent yields of the products.